Research on the Bending Mechanical Properties of Laminated Glass Panels Under Concentrated Loads - Tang Peng; Gong Sai (Engineering Reports)
ABSTRACT In order to study the mechanical properties of glass panel structures applied to automotive bridge decks, this paper conducted bending tests on glass bridge decks under wheel loads. The experiment applied a concentrated load to the center of the plate, with displacement as the control condition for loading. This process was repeated until all layers of the glass plates were completely destroyed. The out‐of‐plane deflection displacement field of the laminated glass plate under lateral load was obtained using the three‐dimensional Digital Image Correlation (DIC) method. The results indicate that the load–displacement relationship of laminated glass panels exhibits a certain degree of nonlinearity. Compared with the load displacement curve of a three‐layer glass structure, the load displacement variation of a two‐layer glass structure is significantly closer to linear. The load–displacement variation of a two‐layer glass structure is significantly closer to linear compared to that of a three‐layer glass structure. The direction of the maximum principal stress almost coincides with the diagonal of the glass plate and only shows significant fluctuations under small loads. The load–stress relationship exhibits certain nonlinear characteristics. By conducting experimental research on three‐layer laminated glass panels subjected to local lateral loads, the static mechanical response law of multilayer laminated glass bridge decks under wheel pressure loads was explored. The experimental results can provide a reference for engineering practice.